PHENOMENOLOGICAL CRITERIA OF DESTRUCTION - KYRYTSYA, Inna (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The paper reviews the known deformability criteria, which have become widespread to assess the probability of failure in both monotonic and nonmonotonic plastic deformation. The most widely used methods of assessing plasticity, in which the dependence of plasticity on the stress state scheme is described by plasticity diagrams. The plasticity diagram is an experimental dependence of the ultimate deformation on the stiffness index of the stress state. In most works, this dependence is represented by a flat curve. The plasticity of metals depends on many factors, namely the nature of the metal and the thermomechanical parameters of the process. With cold plastic deformation, the main factor influencing plasticity is the stress state and the law of its change during loading. To quantify the impact of stress state on the probability of failure using failure criteria. Under the destruction is understood the appearance of macrocracks, which leads to irreparable damage to the product. A common disadvantage of the known deformation criteria, which are common to assess the probability of failure in both monotonic and nonmonotonic plastic deformation is that the subintegral functions of these criteria are based on the hypothesis that the effect of stress state on plasticity is described by the plasticity diagram and the influence of load history - flat trajectories. Due to the fact that the plasticity diagrams cover a rather narrow class of stress states, in applied theories of deformability there is no single approach to estimating the value of the used plasticity resource in the processes of metal forming. From the performed research it follows that at present there are almost very few works in which the dependence of plasticity on the history of loading is described by spatial trajectories. Therefore, the question of the destruction criteria remains open and relevant.